2017
DOI: 10.18203/2394-6040.ijcmph20171746
|View full text |Cite
|
Sign up to set email alerts
|

Female breast cancer in different age groups: clincopathological features and treatment strategies

Abstract: INTRODUCTIONFemale breast cancer is a major public health problem throughout the world. It is the most common cancer type among women in developed and developing countries. Moreover, it is the principal cause of death from cancer among women globally. Nearly 55% of the worldwide burden is now experienced in developed countries, but incidence rates are rapidly rising in developing countries as well. 1According to the annual cancer incidence report published by the Saudi cancer registry, there were 1,853 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The higher rate of BC in young patients in our cohort is comparable with the previous data from Saudi women reported by Nuzhat et al 23 and Elkum et al 24 from Riyadh also observed a higher rate of BC (25.2%-33.2%) in young women in Saudi Arabia than the women from the western countries (3.7%-6.6%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher rate of BC in young patients in our cohort is comparable with the previous data from Saudi women reported by Nuzhat et al 23 and Elkum et al 24 from Riyadh also observed a higher rate of BC (25.2%-33.2%) in young women in Saudi Arabia than the women from the western countries (3.7%-6.6%).…”
Section: Discussionsupporting
confidence: 92%
“…22 However, it is significantly higher than the 3.7%-6.6% reported in many Western countries. [4][5][6][7] The higher rate of BC in young patients in our cohort is comparable with the previous data from Saudi women reported by Nuzhat et al 23 and older patients (p=0.174). IDC: invasive ductal carcinoma, ILC: invasive lobular carcinoma, DCIS: ductal carcinoma in situ, LCIS: lobular carcinoma in situ receptors-positive (p=0.0001, p<0.0001) and more likely to be triple-negative (p=0.008).…”
supporting
confidence: 90%
“…15 Nuzhat in his study, 39 (25.2%) patients were less than or equal to 40 years of age, 60 (38.7%) were more than 40 to 50 years and 56 (36.1%) were more than 50 years of age with the median age at diagnosis being 47 years. 16 Mehradad et al from Iran in the year 2016 recorded data of 258 patients with breast cancer and reported that the mean age of the patients at diagnosis was 44.2 years (range: 25-71 years).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies comparing the two populations have included limited data on patient- and disease-specific characteristics [ 5 , 11 , 12 ]. More importantly, multiple aspects of BC specifics remain to be addressed in these populations.…”
Section: Introductionmentioning
confidence: 99%